Protective factors against oxidative stress in COPD: focus on Nrf2-dependent antioxidant gene expression - Kominkova, Eva; Petrek, Martin; Navratilova, Zdenka (Frontiers in Medicine, 2025)
Chronic obstructive pulmonary disease (COPD) continues to be the world’s primary cause of morbidity and mortality. The main mechanism driving the pathogenesis of COPD is oxidative stress. Antioxidant genes, regulated by the Nrf2/ARE signaling pathway, play a protective role against oxidative stress. Unfortunately, this pathway appears to be dysregulated in COPD, leading to decreased expression of antioxidant genes and persistent oxidative stress. We reviewed numerous studies measuring the expression of antioxidant genes in COPD. We also focused on developments in methods used to study gene expression in COPD over time, along with measuring antioxidant gene expression in various cell types, and the potential use of antioxidant gene expression as a predictor of COPD progression. And last but not least we discussed the association of cigarette smoke exposure with antioxidant gene expression together with antioxidant treatment in COPD. Understanding the altered expression of antioxidant genes in COPD could help in treating COPD, as well as predicting its progression.